Explaining Compensation Satisfaction Among Public Officers from Equity and Expectancy Perspective - Hasrudy Tanjung; Iin Agustina; Hafid Aditya Pradesa (Publik : (Jurnal Ilmu Administrasi), 2022)
Managing compensation is an interesting and sensitive issue in organizations, including public organizations.This study examines the effect of each aspect of compensation on satisfaction among public officers. Based on the equity theory and the expectancy theory, this research focuses on the central concept observed about compensation, with a total of 122 public officials who work in two government agencies in Medan, North Sumatra, participating as respondents. The results showed that among the four aspects of compensation observed and tested in this study, the findings show that only the incentive aspect had an essential effect on employee satisfaction with compensation. The three other aspects of compensation were found to have no significant effect on employee satisfaction with compensation. The practical implication for public officers who work in the public sector, the organizational incentive pattern is very attractive to them. This study also argues that these same challenges can also serve as drivers shaping the future of public compensation as a theory and practice. While conclusion also offers a new perspective in favor of the argument advanced here.